Ivermectin and dexamethasone combination induces apoptosis in SUP-B15 cell line - Siregar, Olga R.; Wahyuni, Arlinda S.; Pasaribu, Ayodhia P.; Edianto, Deri; Ugrasena, I DG.; Amelia, Rina; Lubis, Inke ND.; Rusda, Muhammad (Narra J, 2025)
The development of glucocorticoid resistance has complicated the management of acute lymphoblastic leukemia (ALL), leading to increased mortality rates. Ivermectin, a low-cost and well-established anthelmintic, exhibits anticancer potential and may enhance glucocorticoid toxicity in ALL, offering a possible strategy to overcome resistance. The aim of this study was to evaluate the apoptotic effect of combining ivermectin with dexamethasone in ALL. ALL SUP-B15 cells were cultured under standard conditions before treatment with dexamethasone (200 nM) alone or combined with ivermectin (5, 10, and 20 µM), with an untreated group serving as the control.  Cytotoxicity was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay by measuring cell viability and inhibition. Apoptosis was evaluated through BAX, BCL-2, and CASP3 gene expression analysis using reverse transcription-polymerase chain reaction (RT-PCR). The findings revealed that the combination of ivermectin and dexamethasone was superior in the repression of ALL cell viability compared to control (p<0.001). The combination of dexamethasone 200 nM + ivermectin 20 μM demonstrated the most significant cell inhibition of 38.16±0.04% (p<0.001) and produced the lowest cell viability of 61.84±0.05% (p<0.001). Moreover, the combination of dexamethasone 200 nM + ivermectin 20 μM demonstrated superior upregulations of BAX (p<0.001) and CASP3 (p<0.001). In conclusion, the addition of ivermectin (5 µM) to dexamethasone regimen (200 nM) increases its cytotoxic and apoptotic activities against SUP-B15 cell line as observed by the CASP3 and BAX upregulation. Studies to confirm the enhanced anticancer activity by this combination by observing the protein levels and animal studies are warranted.